Integrating Sharia Economics and Public Administration Content into English Language Teaching (ELT) Materials: A Conceptual Study - Tira Nur Fitria; Afdaleni (ITB AAS INDONESIA Surakarta, 2026)
This study explores a model for integrating Sharia (Islamic) Economics and Public Administration content into English Language Teaching (ELT) materials for students of Islamic Economics. This study employs a conceptual research design. The study shows that recognizing English as the primary medium for international academic and professional communication, the study emphasizes discipline-specific instruction through English for Specific Purposes (ESP) and Content-Based Instruction (CBI). By combining English learning with field-specific content, students develop linguistic competence alongside professional expertise, engaging with specialized terminology such as zakat, waqf, sukuk, and Islamic finance concepts within regulatory and governance contexts. This integrated approach fosters holistic learning, enabling students to enhance reading, writing, speaking, and listening skills while deepening their understanding of economic principles and administrative procedures. It also promotes critical thinking and problem-solving through real-world tasks like case study analysis, debates, and policy brief writing. Furthermore, students gain international competence by accessing global research, participating in conferences, and aligning with Sharia-compliant professional standards. By embedding authentic, discipline-relevant materials into English instruction—including reading, writing, speaking, and listening tasks—learners acquire functional, contextually meaningful language skills that prepare them for academic, professional, and global engagement in Islamic finance and governance. By applying ESP and Content-Based Instruction principles, learners develop discipline-specific vocabulary, critical thinking, problem-solving skills, and holistic competencies across reading, writing, speaking, and listening. This approach enhances students’ ability to engage in international academic and professional discourse while remaining grounded in Sharia-compliant finance and governance. For future research, it is recommended to examine the long-term impact of this integrated approach, explore effective teaching strategies and materials, investigate student motivation and engagement, and consider digital or international learning platforms to further strengthen language and professional skills.